Implementation of International Arbitration Awards in Indonesia : Is it Final and Binding? - Fachrurozy, Azriel; Devano, Aldo; Malida Hany, Elbirra; Prasetya Mega Jaya, Belardo; Justitia, Mentari (International Asia Of Law and Money Laundering (IAML), 2024)
International Arbitration is one of the popular dispute resolutions used by disputing parties because it has several advantages such as confidentiality, fast decision-making and in principle is final and binding. However, in Indonesia, there are still other efforts that must be carried out before the award is executed or implemented so that international arbitration awards in Indonesia are not directly executed or implemented. Therefore, the objectives of this study are: 1), to know and analyse how the implementation of international arbitration awards in Indonesia; 2) to examine how the nature of international arbitration awards in Indonesia. This research was conducted using normative juridical research methods. The results of this study are First, the Implementation of International Arbitration Awards in Indonesia can be recognised and implemented if they are registered with the Registrar of the Central Jakarta District Court, and have fulfilled the requirements in Article 66 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Second, International Arbitration Awards in Indonesia are final because there is no appeal at the High Court level in any province in Indonesia, and cassation or review to the Supreme Court. International Arbitration Awards are binding or enforceable/executable as long as they do not conflict with the provisions of Indonesian national laws and regulations and fulfil the provisions and stages stipulated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, hence international arbitration awards.